Photonic-structured TCO front contacts yielding optical and electrically enhanced thin-film solar cells - Sanchez-Sobrado, Olalla (2020)
COMPETE 2020 Programme and National Funds through FCT (Portuguese Foundation for Science and Technology) under the projects UID/CTM/50025/2019. ALTALUZ ( PTDC/CTM-ENE/5125/2014 ). SuperSolar (PTDC/NAN-OPT/28430/2017). TACIT (PTDC/NAN-OPT/28837/2017). LocalEnergy (PTDC/EAM-PEC/29905/2017). grant SFRH/BPD/114833/2016 .